The energy-growth nexus reinterpreted by access to electricity : The case of African Sub-Saharian countries - (:unkn) unknown (My University, 2019)
Energy demand in Sub-Saharan Africa has outpaced that in the North. The International Energy Agency (IEA) has forecasted the greatest increase in energy consumption to come from this area. The relationship between energy consumption and economic growth began to be studied in Sub-Saharan Africa in the late 90s, using the same method as for developed countries and with the same lack of consensus on the direction of causality. This thesis attempts to clarify this situation through a meta-analysis of fifty articles published since 1996 to 2016. This meta-analysis involves five analytical categories: type of publication, geographical area studied, econometrics method used, energy consumption indicators, and control variables. Each of these dimensions includes many disaggregated variables. Logistic regressions are run on the variables presented above for each of the four causality hypotheses. In research that studies single countries, the likelihood of finding for a given causality hypothesis is very sensitive to the econometric method implemented. Findings on a panel of countries are then presented; their methods assert the neutrality hypothesis.The energy sector in sub-Saharan Africa is in a state of flux. Based on an approach borrowed from industrial economics, using historical examples that point to three successive transformations of electricity market structure, our analysis differs from previous studies by looking at demand as a consequence of supply. Our results show, an extremely fragmented demand for energy in sub-Saharan African countries,within which a very dynamic unmet demand drives change in how supply is offered. New forms of energy provisioning introduced on the electricity market put into question the initial on-grid network model. The appearance of decentralized electricity production shows that there is a potential for going beyond current limitations and moving away from a supply structure focused on the maintenance and improvement of on
Keywords: African Research